The Role of Human Capital in Innovative Economic Development - TUREKULOVA, Dametken M.; MUKHAMBETOVA, Lyazzat K.; SATKANOVA, Rimma G.; LESBAYEVA, Gulnara T.; ZHANAKOVA, Nazigul N.; SADU, Zhanna (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
The research is relevant because the human place in the economy largely determines the level of industrial, economic, and social development. The theory of human capital in its modern interpretation has certain prerequisites and logically results from the development of the world philosophical and economic thought. Therefore, before studying the modern concepts and interpretations in the field of human capital, it is necessary to investigate the evolution of scientific views of the problem of human productive capacities and their use in public production. This research aims to systematize the interpretations of the ‘human capital’ concept and discover the interrelations between the indicators of human development and the level of innovative activity. The study analyzes the theoretical approaches to the definition of the ‘human capital’ concept, presents their comprehensive assessment, and outlines the objective prerequisites for the development of scientific ideas regarding the theory of human capital. In addition, the interrelation of innovative development indicators and the human development index was proven based on economic and mathematical modeling using canonical analysis. The obtained results can be used to further develop generalized conceptual models when managing innovative and modernization processes, based on the activation of the human capital in modern economic systems.
Keywords: workforce; knowledge management; transition to innovation economy; human development index; European innovation scoreboard